Physical capacity modulates intestinal barrier dysfunction in functional disorders: phenotype-specific patterns in fibromyalgia and irritable bowel syndrome - Russo, Francesco; Bianco, Antonella; Prospero, Laura; Laselva, Gaetana; Grasso, Marco; D’Attoma, Benedetta; Verrelli, Nicola; Ignazzi, Antonia; Franco, Isabella; Goscilo, Francesco; Bagnato, Claudia Beatrice; Ancona, Anna; et al. (Frontiers in Physiology, 2025)
BackgroundIntestinal barrier dysfunction is increasingly implicated in the pathophysiology of fibromyalgia (FM) and irritable bowel syndrome (IBS), particularly in their comorbid form. Physical capacity (PC) influences systemic inflammation and metabolic resilience, but its relationship with gut barrier integrity in these conditions remains poorly defined.MethodsWe conducted a cross-sectional study of 56 patients with FM (n = 14), IBS (n = 23), or both (FM + IBS, n = 19). Intestinal barrier function was assessed using serum and fecal zonulin, intestinal fatty acid-binding protein (I-FABP), and the lactulose/mannitol (Lac/Man) urinary excretion test. PC was quantified using the Global Physical Capacity Score (GPCS). Clinical symptoms were evaluated using the Fibromyalgia Impact Questionnaire–Revised (FIQ-R) and IBS Severity Scoring System (IBS-SSS).ResultsFM + IBS patients exhibited the greatest barrier dysfunction, with elevated fecal zonulin and Lac/Man ratio. IBS patients showed increased I-FABP, consistent with epithelial injury, whereas FM patients had milder gastrointestinal symptoms and less pronounced biomarker alterations. Although overall PC scores did not significantly differ across groups, serum zonulin levels showed a strong inverse correlation with GPCS. When stratified by GPCS (cut-off ≥6), patients in the high PC group exhibited significantly lower (p = 0.01) serum zonulin concentrations (48.23 ± 12.44 ng/mL) compared to those in the low PC group (57.63 ± 9.69 ng/mL). Multiple regression analysis confirmed GPCS as an independent predictor of serum zonulin (β = −9.67, p = 0.01), while BMI was not a significant contributor (p = 0.79). Furthermore, urinary indole levels correlated positively with both lactulose excretion and the Lac/Man ratio, supporting the existence of a dysbiosis-permeability feedback loop in these disorders.ConclusionIntestinal barrier dysfunction in FM and IBS displays phenotype-specific patterns and is significantly modulated by PC. These findings support the integration of PC assessment into clinical phenotyping and highlight potential targets for personalized management of chronic overlapping pain syndromes.